RESPON PEMBERIAN PUPUK ZA DAN PUPUK NPK 15.15.15 TERHADAP PERTUMBUHAN PEMBIBITAN KAKAO (Theobroma cacao L.) KLON RCL DALAM POLYBAG - Badrul Ainy Dalimunthe (UNIVERSITAS LABUHANBATU, 2019)
One of the factor that determine the quality of cocoa seed is fertility of growing of medium. Fertility of growing medium can be increase with fertilization by using of ZA fertilizer and of NPK 15.15.15 fertilizer be expected to increase cocoa seedlings. This research was carried out in Bukit Perjuangan Village, Rantau Utara Sub District of West Labuhanbatu, East of Nort Sumatera in April – June 2013 using randomize complete block design with two factors. The first factor is ZA fertilizer (0, 0.5, 1, 1.5 gr/polybag) and the second factor is NPK 15.15.15 fertilizer (0, 2, 4 gr/polybag). Parameter observed were plant height, stem diameter, number of leaves, and leavea area. From the research, of ZA fertilizer unsignificantly affect on all parameters. of NPK 15.15.15 fertilizer significantly affect plant height, stem diameter, number of leaves and leaves area. Interaction of ZA fertilizer and of NPK 15.15.15 fertilizer unsignificantly affect on all parameters. The result from this experimental were obtained in the treatment of ZA fertilizer at no ZA fertilizer application ( Z0 ) and of NPK 15.15.15 at no NPK 15.15.15 fertilizer application ( P0 ). Keywords : ZA fertilizer, NPK 15.15.15 fertilizer, cocoa seedlings.